POTENSI WISATA KULINER KOTA MUNTILAN, Studi Kasus : Wisata Kuliner di Koridor Jalan Veteran - Pribadi, Gerry Hutama (Jurnal Arsitektur Komposisi, 2018)
Abstract: Culinary diversity on the Veteran road creates the city of Muntilan known to have unique culinary tours. As a result, culinary tours grow in Muntilan and become an attractive tourism alternative. The objective of the research is to identify the culinary potential in the Veteran street corridor, to become more known in the world of tourism. The research is descriptive qualitative, using primary and secondary data. Primary data were obtained through field observations, mapping and interviews. The interview process was conducted on the citizens of Veteran Street corridor, Muntilan city residents, heads of street vendors organizations, and culinary tour visitors. Secondary data is obtained from government documents and journal articles. The results show, culinary tourism in the corridor of Veteran street in Muntilan has unique by its history, culture and social aspects.Keywords: culinary tourism, tourism, Veteran street corridorAbstrak: Keanekaragaman kuliner di jalan Veteran menciptakan kota Muntilan dikenal memiliki wisata kuliner unik. Akibatnya, wisata kuliner tumbuh di Muntilan dan menjadi alternatif wisata yang menarik. Tujuan penelitian adalah mengidentifikasi potensi kuliner di koridor Jalan Veteran, agar semakin dikenal dalam dunia wisata. Penelitian bersifat deskriptif kualitatif, menggunakan data primer dan sekunder. Data primer diperoleh melalui pengamatan lapangan, pemetaan dan wawancara. Proses wawancara dilakukan pada warga koridor jalan Veteran, warga kota Muntilan, ketua organisasi pedagang kaki lima, dan pengunjung wisata kuliner. Data sekunder diperoleh dari dokumen pemerintah dan artikel jurnal. Hasil penelitian menunjukkan, wisata kuliner di koridor jalan Veteran di Muntilan unik dilihat dari aspek sejarah, budaya dan sosial.Kata kunci: wisata kuliner, pariwisata, koridor jalan Veteran